Continuity as patterning: A process perspective on continuity. (February 2022) - Feldman, Martha S; Worline, Monica; Baker, Natalie; Lowerson Bredow, Victoria
This article extends previous research on how work continues in the face of disruption by theorizing continuity as patterning and highlighting the difference between continuity of a thing and continuity as a process. Based on interviews with people who continued providing mental health care during and after the disruption caused by Hurricane Katrina, we show that continuity is a dynamic process that entails people orienting to what actions they can take and how they can connect these actions into paths in an unfolding material, social, and personal situation. The paths, taken together, are a pattern of work (in our case, a pattern of mental health care). While recognizing that exogenous goals play a role, we highlight the importance of the endogenous experience of an activity in taking action and creating paths. Viewing continuity as patterning suggests new roles for organizations in supporting flexible responses to disruption.